Gaya Hidup Hedonis Mahasiswa: Bagaimana Kontribusi Kontrol Diri dan Konformitas Teman Sebaya? - Ishlakhatus Sa’idah; Sri Rizqi Wahyuningrum; Diana Vidya Fakhriyani; Aisa, Anna (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2024)
A hedonic lifestyle is one where every activity is related to pleasure or life satisfaction. One of the factors that influences a hedonic lifestyle is self-control and peer conformity. This research aims to determine the influence of self-control and peer conformity on hedonic lifestyles and to find out how much influence self-control and peer conformity have on hedonic lifestyles in students. The research method used is quantitative research. The location of this research is the Tarbiyah Institute of the Madura State Islamic Religion Faculty. Sampling in this study used a purposive random sampling technique. The respondents in this research were 137 students. Data collection techniques included the Self-Control Scale, the Peer Conformity Scale, and the Hedonic Lifestyle Scale. The data analysis technique used is multiple linear regression analysis using SPSS software. The results of this study show: first, self-control and peer conformity influence students’ hedonic lifestyles (Ha accepted). The basis for making this decision is the significance value of self-control (0.000 < 0.05) and the significance value of peer conformity (0.001 < 0.05); secondly, the variables self-control (X1) and peer conformity (X2) simultaneously influence the hedonic lifestyle variable (Y) by 42.7%. Meanwhile, it is possible that it is influenced by other variables outside the variables that were not examined in this research.